Edukasi Literasi Keuangan Syariah untuk Meningkatkan Kompetensi Perempuan Pelaku Usaha Kreatif di Kabupaten Jepara: Indonesia - Nur Huda; Nur Khoirin; Siti Mujibatun; Ana Zahrotun Nihayah; Lathif Hanafir Rifqi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance Islamic financial literacy competencies among women creative entrepreneurs in Jepara Regency through a service-learning approach. The program was implemented through educational sessions, interactive training, and case-based simulations involving 40 participants. The evaluation instrument consisted of a closed-ended questionnaire based on a 5-point Likert scale, and the data were analyzed descriptively by calculating mean scores and the percentage of achievement for each indicator. The results of the program indicate that participants’ understanding of Islamic financial principles reached 85%, comprehension of the differences between Islamic and conventional financial systems reached 90%, interest in adopting Islamic financing reached 80%, confidence in financial decision-making reached 75%, and readiness to use Islamic contracts reached 80%, demonstrating significant achievements. Overall, this community service activity had a positive impact in encouraging the sustainable adoption of Islamic finance, thereby supporting the development of creative enterprises in Jepara.